Effective Dose of Prophylactic Oxytocin Infusion During Cesarean Delivery in 90% Population of Nonlaboring Patients With Preeclampsia Receiving Magnesium Sulfate Therapy and Normotensives: An Up-Down Sequential Allocation Dose-Response Study. (1st September 2021) - Tyagi, Asha; Mohan, Aparna; Singh, Yuvraj; Luthra, Ankit; Garg, Devansh; Malhotra, Rajeev Kumar
Abstract : BACKGROUND: Oxytocin administration during cesarean delivery is the first-line therapy for the prevention of uterine atony. Patients with preeclampsia may receive magnesium sulfate, a drug with known tocolytic effects, for seizure prophylaxis. However, no study has evaluated the minimum effective dose of oxytocin during cesarean delivery in women with preeclampsia. METHODS: This study compared the effective dose in 90% population (ED90) of oxytocin infusion for achieving satisfactory uterine tone during cesarean delivery in nonlaboring patients with preeclampsia who were receiving magnesium sulfate treatment with a control group of normotensives who were not receiving magnesium sulfate. This prospective dual-arm dose-finding study was based on a 9:1 biased sequential allocation design. Oxytocin infusion was initiated at 13 IU/h, on clamping of the umbilical cord, in the first patient of each group. Uterine tone was graded as satisfactory or unsatisfactory by the obstetrician at 4 minutes after initiation of oxytocin infusion. The dose of oxytocin infusion for subsequent patients was decided according to the response exhibited by the previous patient in the group; it was increased by 2 IU/h after unsatisfactory response or decreased by 2 IU/h or maintained at the same level after satisfactory response, in a ratio of 1:9. Oxytocin-associated side effects were also evaluated. Dose-response data for the groups were evaluated using a log-logistic function and ED90 estimates were derived from fitted equations using the delta method. RESULTS: The ED90 of oxytocin was significantly greater for the preeclampsia group (n = 27) than for the normotensive group (n = 40) (24.9 IU/h [95% confidence interval CI, 22.4–27.5] and 13.9 IU/h [95% CI, 12.4–15.5], respectively); the difference in dose requirement was 10.9 IU/h (95% CI, 7.9–14.0; P < .001). The number of patients with oxytocin-related hypotension, defined as a decrease in systolic blood pressure >20% from baseline or to <90 mm Hg, was significantly greater in the preeclampsia group (92.6% vs 62.5%; P = .030), while other side effects such as ST-T depression, nausea/vomiting, headache, and flushing, were not significantly different. There was no significant difference in the need for additional uterotonic or uterine massage, estimated blood loss, and need for re-exploration for uncontrolled bleeding. CONCLUSIONS: Patients with preeclampsia receiving preoperative magnesium therapy need a greater intraoperative dose of oxytocin to achieve satisfactory contraction of the uterus after fetal delivery, as compared to normotensives. Abstract :